2009
DOI: 10.1063/1.3257639
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific behavior in de-excitation spectra of F3SiCH2CH2Si(CH3)3 in the Si 1s excitation region

Abstract: Excitation (total ion yield) and de-excitation (resonant photoemission) spectra have been measured in the Si 1s photoexcitation region of the F(3)SiCH(2)CH(2)Si(CH(3))(3) molecule using monochromatized undulator radiation. Theoretical calculations within the framework of density functional theory have reproduced the observed total ion yield spectrum very well. The first peak at the lowest photon energy, coming from Si 1s excitation at the trimethyl side into a vacant orbital, induces spectator Auger decays in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The term KE means the electron kinetic energy. This spectator transition has been found in SiF 4 and related molecules with the Si atom, as described previously [11][12][13].…”
Section: Electron Emission Spectrasupporting
confidence: 79%
See 1 more Smart Citation
“…The term KE means the electron kinetic energy. This spectator transition has been found in SiF 4 and related molecules with the Si atom, as described previously [11][12][13].…”
Section: Electron Emission Spectrasupporting
confidence: 79%
“…The analysed spectra provided energies of doubly charged molecular ions having two Si 2p holes and indicated that a state of 1 D 2 in the atomic representation had the dominant intensity [9]. Since simple spectra were measured for resonant KLL Auger transitions, an energy transformation of photoexcited states into electron kinetic energies was elucidated in spectator resonant KLL Auger electrons of SiF 4 and similar molecules [11][12][13]. On the other hand, post-collision interaction (PCI) takes place near the ionization threshold, which induces distortion of peak shapes of NA components and re-capture of a slow core photoelectron.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that monochromatic photoexcitation of Si-containing molecules yields a simple spectrum for resonant Auger transitions from Si K-shell excited states. Our previous study using the F 3 SiC 2 H 4 Si(CH 3 ) 3 molecule indicated that some photoexcited states of Si 1s electrons decomposed into different states of singly charged ions with two 2p holes during resonant Auger decays [12]. This decomposition yielded a spectator electron existing in some Rydberg orbitals and/or valence molecular orbitals.…”
Section: Introductionmentioning
confidence: 98%
“…Inner-shell excited or ionized molecules dissociate into fragment ions following Auger electron emission. If the Auger decay process depends highly on the core-hole states, there is a high probability of producing fragment ions distinctive to the particular atomic site of excitation or ionization [16][17][18].…”
Section: Introductionmentioning
confidence: 99%